IDENTIFIKASI INTRUSI AIR LAUT PADA AKUIFER MENGGUNKAN METODE GEOLISTRIK - Iyu Suknawati; Usman Malik (Universitas Riau, 2023)
The identification of the effect of seawater intrusion on aquifers on groundwater depth using the geoelectrical dipole-dipole configuration method has been carried out in Tanjung Kapal Village, Rupat Bengkalis. In this study, the length of the track used is 100 meters. data retrieval used are resistivity meter, resulting current data (I) and potential difference (V). Data processing uses Res2divn software which results in the form of image resistivity, 2D resistivity below the surface. This track has a distance of 200 m from the coast with resistivity values ranging from 0.726 –351 Ωm. Interpretation results show that there is sea water intrusion on this line as evidenced by its resistivity value. The resistivity value of rocks affected by intrusion on track is 0.726 – 4.26 Ωm. The results of the quality of groundwater that have been tested are classified as brackish. Well water is not suitable for human consumption. correspondingto the test results of well water samples showed a pH value of 7.0 and a salinity of 0.22%.